Pollination system of Masdevallia hortensis Luer & R. Escobar. (Orchidaceae: Pleurothallidinae) in a cloud mountane forest of the Cordillera Occidental, in Colombia (2020)
Although pleurothallids are among the most diverse groups of orchids, their pollination ecology has been studied in only nine of the 42 recognized genera. Pollination by deception has been assumed as the generality for this group despite pleurothallids exhibit diverse pollination systems involving a vast assortment of different flies. However, considering that this is such a diverse group, the generalization about pollination systems based on few studies likely represents an overestimation of the deception cases whereby floral rewards offered to pollinators may not be conspicuous. Métodos. we study the pollination system of Masdevallia hortensis in field conditions in a cloud forest in the Cordillera Occidental in the Colombian Andes, in the buffer zone of National Natural Park Tatamá. We recorded information such as flowering patterns, mating systems, behavioral observations of potential pollinators and floral keys involved in the pollination system. Resultados. Masdevallia hortensis produces sugary secretions in the lateral sepals along purple dotted lines, on which visiting flies feed. The concentration of these secretions containing sucrose varies according to the time of the day. Furthermore, depending on whether the pollinaria was already removed, these dots maintain visitors and guide them towards the chamber between the mobile lip and the column, in which a single species of fly (Drosophilidae sp. 1 AO) is trapped until it manages to free itself with the pollinaria already attached to its sub-scutellum . We also show that M. hortensis is strictly self-incompatible, which makes fly pollination an essential process for the maintenance of natural populations. Discusión y conclusiones. Masdevallia hortensis showed a sophisticated and customized pollination mechanism. Along with other groups of pleurothallids, Masdevallia hortensis offers rewards to their visitors, an aspect that should be evaluated in other Masdevallia species. In this way, integrative ecological studies will strengthen the natural history knowledge and evolutionary patterns of this group of orchids.